Contesting Race and Citizenship Youth Politics in the Black Mediterranean - Hawthorne, Camilla (Cornell University Press, 2022)
Contesting Race and Citizenship is an original study of Black politics and varieties of political mobilization in Italy. Although there is extensive research on first-generation immigrants and refugees who traveled from Africa to Italy, there is little scholarship about the experiences of Black people who were born and raised in Italy. Camilla Hawthorne focuses on the ways Italians of African descent have become entangled with processes of redefining the legal, racial, cultural, and economic boundaries of Italy and by extension, of Europe itself. Contesting Race and Citizenship opens discussions of the so-called migrant "crisis" by focusing on a generation of Black people who, although born or raised in Italy, have been thrust into the same racist, xenophobic political climate as the immigrants and refugees who are arriving in Europe from the African continent. Hawthorne traces not only mobilizations for national citizenship but also the more capacious, transnational Black diasporic possibilities that emerge when activists confront the ethical and political limits of citizenship as a means for securing meaningful, lasting racial justice-possibilities that are based on shared critiques of the racial state and shared histories of racial capitalism and colonialism.